Life Cycle Assessment of Methanol Production from Municipal Solid Waste: Environmental Comparison with Landfilling and Incineration - Cristiano Queiroz Cerqueira; Electo Eduardo Silva Lora; Lidiane La Picirelli de Souza; Márcio Montagnana Vicente Leme; Regina Mambeli Barros; Osvaldo José Venturini (Resources)
Inadequate waste management strategies play a significant role in exacerbating environmental challenges, such as increased greenhouse gas emissions, resource depletion, and other adverse ecological impacts. These issues are aggravated by the global rise in municipal solid waste (MSW) generation, surpassing the rate of population growth. Simultaneously, there is an urgent demand for sustainable energy solutions to combat climate change and its wide-ranging impacts. In response, this study addresses a critical question: is methanol production from MSW, a waste-to-chemical (WtC) alternative based on circular economy principles, a more environmentally sustainable approach compared to traditional waste-to-energy (WtE) methods like landfilling with biogas recovery and incineration? To answer this, this study evaluates the environmental performance of MSW-to-methanol technologies using life cycle assessment (LCA), focusing on key indicators such as global warming potential, resource depletion, and impacts on human health and ecosystem quality. The results reveal that methanol production from MSW significantly reduces global warming potential (GWP) by 87% compared to landfilling and 56% compared to incineration. Additionally, the process demonstrates high energy efficiency in electricity generation, achieving 80% of the output of incineration. These findings position MSW-to-methanol as a promising alternative for advancing sustainable waste management and renewable energy transitions. While the technology is still in its developmental stages, this research highlights the need for further advancements and policy support to enhance feasibility and scalability. By providing a comparative environmental analysis, this study contributes to identifying innovative pathways for addressing pressing waste management and energy sustainability challenges.